TERMINAL-24 Score in Predicting Early and In-hospital Mortality of Trauma Patients; a Cross-sectional - Ashrafian Fard, Sadegh; Ahmadi, Sajjad; Ebrahimi Bakhtavar, Haniyeh; Sadeghi Bazargani, Homayoun; Rahmani, Farzad (Archives of Academic Emergency Medicine, 2025)
Introduction: Determining the trauma patients’ prognosis is crucial for patients’ safety, triage, and appropriate management. This study aimed to evaluate the screening performance of Traumatic Emergency Room Major Injury Death At Least 24 hours (TERMINAL-24) score in predicting the mortality of trauma patients. Methods: This cross-sectional study was conducted in the emergency department (ED) of a referral trauma center, between October 2023 and September 2024. The main goals of the project were determining the value of TERMINAL-24 score in predicting early (within 8 hours of admission to ED) and in-hospital mortality of multi-trauma patients as well as comparing the accuracy of TERMINAL-24 with other trauma severity scores (GAP, RGAP, NTS) in this regard. Results: 963 multi-trauma patients were included in this study. The mean age of the patients was 37.75±17.10 years (73.2% male). 55 patients died in the emergency department and 46 patients died during hospitalization in other departments. Male gender (p = 0.009), older age (p =0.011), traffic accidents (p = 0.005), more critical vital signs (p = <0.001), admitting in neurosurgery ward (p < 0.001), and higher trauma severity (P < 0.001) were significantly associated with higher mortality rate. The area under the curve (AUC) of TERMINAL-24 score in predicting early and in-hospital mortality of trauma patients were 0.964 (95%CI: 0.937-0.991) and 0.954 (95%CI: 0.925-0.983), respectively. The specificity and sensitivity of TERMINAL-24 score for predicting early mortality at its best cut-off point (cut-off = 2.5) were 95.04% (95%CI: 93.43-96.28) and 96.36% (95%CI: 87.63-99.35), respectively. For predicting in-hospital mortality, these measures were 98.84% (95%CI: 97.88–99.37) and 87.13% (95%CI: 79.22-92.32), respectively (best cut-off = 2.5). Conclusions: It seems that, TERMINAL-24 score has the same accuracy in predicting both early and in-hospital outcomes of trauma patients. Considering the calculation formula of this score and its simplicity, it can be used in pre-hospital and in-hospital settings to predict the outcome of trauma patients.